Inferiority Feeling Serta Aktivitas Fisik Siswa Obesitas dan Implikasi Pelayanan Bimbingan dan Konseling - Iqbal Arrahman; Firman Firman; Netrawati Netrawati (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
This study aims to find out how to accept Class IX students. The purpose of this study was to increase students' low self-acceptance compared to their classmates. This study used case study methods. which means that the actual conditions that are evident in a situation and the conditions for this study to collect data are by interviewing, In addition, the role of guidance and counseling teachers in handling problems of students with low self-acceptance is to spread AUM (Problem Revealing Tool) to find out the problems that students are experiencing as early as possible. Six of the students who have low self-acceptance have slowly shown the results of their blending in with their friends and starting to participate in activities held both at school and around the residence.